Порівняльна оцінка перебігу раннього поопераційного періоду після операцій на щитоподібній залозі, виконаних зі стандартного та мінімального інвазійного доступів - Чернишов, С. В.; Щупачінська, Л. О.; Мельник, А. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
Syndrome of post-operative nausea, vomiting and pain in the early postoperative period in patients who underwent hemithyroidectomy were analyzed. Surgical interventions were performed using two different approaches to the thyroid gland: a standard by Kocher and minimally invasive own technique. It is concluded that after hemithyroidectomy post-operative nausea and vomiting can occur for many reasons and are not significantly determined by the nature of surgical access to the thyroid gland, post-operative pain in the occipital region and the back of the neck after hemithyroidectomy significantly less common in minimally invasive procedure especially in patients over 40 years old.